Feeling bad or feeling good, does emotion affect your consumption of food? A meta-analysis of the experimental evidence. (September 2018) - Evers, Catharine; Dingemans, Alexandra; Junghans, Astrid F.; Boevé, Anja
Highlights: A meta-analysis assessed the effect of negative and positive emotions on eating. Several subgroups were included, e.g., (non) eating disordered individuals. Negative emotions increased eating in restrained eaters (medium effect). Positive emotions increased eating in general (small effect). Emotion induction, eating measures and age explained heterogeneity. Abstract: Whether emotions affect eating, and in whom, has remained unclear. This meta-analysis assessed the effect of emotions on eating in both healthy and eating disordered individuals. Fifty-six experimental studies investigating the causal effect of emotions on eating behavior were selected including 3670 participants. Separate meta-analyses (random models) were performed for negative and positive emotions. Among healthy people the moderating impact of individual differences in restrained and emotional eating and of being overweight or obese was assessed for negative emotions. Results: Restrained eaters showed increased eating in response to negative emotions. Negative emotions did not affect eating in overweight or obese people, people with eating disorders or in self-assessed emotional eaters. Positive emotion resulted in increased eating across groups. Heterogeneity was high and could be explained by differences in emotion induction procedures, eating measures, and age of participants. These findings indicate that particularly restrained eaters are vulnerable to emotion-induced eating. Additional qualitatively good experiments are called for in combination with studies assessing emotion-eating links in people's naturalistic environment.